Membentuk Karakter Integritas Anak Usia 7-9 Tahun Melalui Permainan Tradisional - Rizqytasari Putri; Gregorius Ari Nugrahanta (Universitas Negeri Makassar, 2023)
This studied aimed to develop an integrity character education manual based on traditional games for children aged 7-9 years. The researched method used was development researched (RnD) ADDIE type. The results of the studied showed that, 1) the integrity character education manual based on traditional games for children aged 7-9 years was developed used the ADDIE step, 2) The overall quality of the manual obtained a score of 3.82 (scale 1-4) with the qualification